A broadband beam‐steerable Fabry–Pérot antenna employing water‐based reconfigurable partially reflective surface - Jiali Yan; Zhiming Liu; Huilin Zhou; Yuhao Wang; Hao Xu (IET Microwaves, Antennas & Propagation)
Abstract A novel broadband water‐based Fabry–Pérot (FP) antenna with beam‐steerable technology is proposed. The antenna consists of a water‐based reconfigurable partially reflective surface (RPRS) and a source antenna. The proposed water‐based RPRS has 13 columns of microfluidic channels inside. The water‐based RPRS achieved 1‐D beam steering by regulating phase distribution through the injection of water into its microfluidic channels. The antenna has exhibited a 10‐dB impedance bandwidth from 5.07 to 6.46 GHz (a fractional bandwidth of 24.1%). This design achieves a beam steering from −11° to +11° in the elevation plane, with measured realised gains over 10 dBi. To verify the correctness of the design, an antenna prototype was fabricated. The measured results are in good agreement with the simulated results, confirming the accuracy of the design principle. The measured results demonstrate that the main beam of the antenna prototype tilts to −12° in the broadside direction.